1991
DOI: 10.1159/000154599
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Histamine Receptors is Associated with Amylase Secretion and Calcium Mobilization in Guinea-Pig Pancreatic Acinar Cells

Abstract: An investigation was made on the effects of histamine and related receptor agonists and antagonists on amylase secretion and Ca2+ mobilization in isolated guinea pig pancreatic segments and acinar cells. The effect of acetylcholine (ACh) was examined for comparison. Histamine evoked marked dose-dependent increases in amylase secretion and small changes in 45Ca2+ efflux, 45Ca2+ influx and intracellular free Ca2+ concentration [Ca2+]i, compared to much large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1992
1992
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…A. Pariente significant rise in enzyme secretion. Similar findings have been obtained by us in guinea-pig pancreatic segments [8,14] and lobules [15]. Furthermore, Lorenz et al [12] showed that the dog pancreatic juice obtained by stimulation by secretin and pilocarpine contains histamine in a high concentration which is constant during the whole secretion period.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…A. Pariente significant rise in enzyme secretion. Similar findings have been obtained by us in guinea-pig pancreatic segments [8,14] and lobules [15]. Furthermore, Lorenz et al [12] showed that the dog pancreatic juice obtained by stimulation by secretin and pilocarpine contains histamine in a high concentration which is constant during the whole secretion period.…”
Section: Introductionsupporting
confidence: 81%
“…Although Harvey and Owen [24] demonstrated vascular effects for histamine, it is worth noting that there was no sustained disturbance in blood pressure during the experiments. Moreover, previous studies have demonstrated that histamine can elicit an increase in amylase secretion from pancreatic segments [14], lobules [3,15] and acinar cells [8]. Nevertheless, we cannot reject that a part of the effects observed in this study may be due to changes in the mesenteric circulation.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In isolated guinea pig pancreatic segments, the H 2 receptor antagonist, oxmetidine stimulated amylase secretion in a dose-dependent manner, similar in magnitude to histamine whereas the H 1 receptor antagonist, chlorpheniramine was only effective at a pharmacological concentration of 10 ¹2 M [40]. In both the anaesthetized rabbit [35] and isolated guinea pig segments [40], application of selective H 1 receptor agonist, 2-thiazolyl-ethylamine resulted in marked increases in exocrine pancreatic secretion whereas the selective H 2 agonist, dimaprit had little or no effect.…”
Section: Effects Of Selective Histaminergic Agonists and Antagonistsmentioning
confidence: 93%
“…Histamine can stimulate pancreatic juice secretion in the isolated dog pancreas [31], the anaesthetized dog [32,33], rabbit and guinea-pig [23,[34][35][36] but it is less effective as a secretagogue in the anaesthetized rat [37] and conscious dog [38]. In the in vitro pancreatic lobules of rabbit [28], segments of guinea pig [39,40] and rat [41] histamine can evoke marked increases in amylase secretion. Similarly, in guinea pig pancreatic acini the paracrine hormone can stimulate amylase output in a dose-dependent manner with maximal effect at 10 ¹3 M [30,42].…”
Section: Effect Of Histaminementioning
confidence: 99%